Share The Formula You Found

+Label +Description

Recently Referred Formulae

lnC=-ke\cdot t lnC_0
(\nabla_{xy}^2 n^2k^2)\psi-2ik(h\cdot\nabla)\psi=0
\overline{a   b} &=& \rm{Re}(a)   \rm{Re}(b) - (\rm{Im}(a)   \rm{Im}(b)) \; i \\
&=& \rm{Re}(a) -  \rm{Im}(a) \; i   \rm{Re}(b) -  \rm{Im}(b) \; i \\
&=& \overline{a}   \overline{b}
\overline{a * b} &=& \rm{Re}(a) \rm{Re}(b) - \rm{Im}(a)\rm{Im}(b) - (\rm{Re}(a) \rm{Im}(b)   \rm{Re}(b) \rm{Im}(a)) \; i \\
&=& \overline{a} * \overline{b}
&&x = \sqrt{D}, \\
&&p_0 = 0, \\
&&q_0 = 1, \\
&&a_k =\lfloor \frac{x   p_k}{q_k} \rfloor, \;\; k \ge 0, \\
&&p_{k 1} = a_k Q_k - p_k, \;\; k \ge 0, \\
&&q_{k 1} = \frac{D  - p_{k   1}^2}{q_k}, \;\; k \ge 0.